Pengaruh Peran Orang Tua Terhadap Perkembangan Moral Anak Usia 4-6 Tahun di Kelurahan Maulafa, Kota Kupang - Maria Delariska Uskuluan; Abdul Syukur; Yohana Yuniati; Gokma N. Tampubolon (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to determine the influence of parental roles on moral development in children aged 4-6 years old Maulafa Village, Kupang City. The role of parents is the skill of parents in educating children to grow their potential in various fields, especially in the aspect of moral development. This type of research is quantitative with the Expo-facto method where this study seeks to determine the relationship between parental roles and moral development with a sample of 22 parents. Where data collection in the study used a questionnaire distributed directly to parents, the research instrument used has been tested for validity and reliability and the data was analyzed using a normality test and a simple linear regression test was carried out, and the test results showed an influence Based on the test results, the data shows that there is an influence of parental roles on moral development in children aged 4-6 years, this can be seen from the value of the simple linear regression test, namely the sig value of 0.000 <0.05.